"I Will Not Be Father Castañeda of ’20, I Will Be Father Castañeta of ’52.” Burlesque Press in Post-Caseros Buenos Aires. (Res Gesta, 2025)
Padre Castañeda is part of the Buenos Aires burlesque press that emerged after Caseros. General studies of the period mention it. However, there are no works that analyze it specifically. This article examines aspects related to its emergence and its members. I propose to show that it is a newspaper that evokes the figure of the writer Francisco Castañeda, not rhetorically, but rather in a way that attempts to draw on some aspects of that public experience developed during the 1820s and the 1820s. This appeal to his figure certainly justifies some aspects of its journalistic strategy. I also postulate that its members had prior public experience at the end of the Rosismo era and that from it emerged some elements that continue in their journalistic practice after Caseros. As a hypothesis, this work aims to show that Caseros, at least from the perspective of the press, does not constitute a marked watershed. In the journalistic world, in several cases, a sort of line of continuity in change is presented. For this reason, there are movements of adaptation and writings that somewhat overact their rejection of Rosismo. The basic source used refers to various newspapers from the period analyzed, but also to some periodicals from Buenos Aires in the 1820s.
Keywords: Press; Caseros; Buenos Aires; Politics